Determination of the Specific Surface Acidity of Al2O3 / CdO System by TPD Method using Pyridine as a Base (Latakia University Journal -Basic Sciences Series, 2018)
In this work, six different samples of the  Al2O3 / CdO system were prepared in a co-precipitation method. Samples were prepared from saturated solutions for cadmium and aluminum salts using concentrated ammonia as a precipitating agent at pH = 8 and after settling and drying the sample was calcined at 400°C for two hours.In order to studied the surface acidity by temperature programmed desorption (TPD) method. The calcined sample was divided to two parts: The TG-DTA measurements was carried on for the first part in order to determine the loss weight using thermal program in the range 20-900°C and 10°C/min. The second part was impregnated in pyridine for 24h, and dried at 120°C to remove the physical adsorbed pyridine and the TG-DTA measurements were performed at the same conditions for the first part.Differential curves were studied to calculate the weight loss produced by the desorption  of pyridine. The AC8 (1-1) showed the highest surface acidity value (0.47m.mol / g), while the sample AC8 (1-0.25) gave the lowest acidity surface value (0.11m.mol / g).